Perlindungan Hukum Bagi Konsumen atas Pelanggaran Hak Informasi Penjualan Produk di Gerai Donat J.CO Indonesia - Januarilla, Jahra’ Marwah; Wulansari, Retno (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyze whether business actors in J.CO Indonesia outlets have fulfilled consumer rights and carried out their obligations as stipulated in Law No. 8 of 1999 concerning Consumer Protection. This study also examines the legal consequences faced by business actors if these obligations are not implemented, and examines the form of legal protection and responsibility of business actors towards consumers, especially in cases of violation of information rights. This study uses a normative legal method with a statutory approach and case studies. The case analyzed involves product promotions at J.CO Indonesia, where business actors provide unclear and misleading price information related to product packages. The analysis focuses on Article 4 letter c, Article 7, and Article 9 of the Consumer Protection Law, which regulate the obligations of business actors to provide correct, clear, and transparent information. The results of the study indicate that J.CO Indonesia business actors have violated their legal obligations by presenting misleading information to consumers, resulting in material losses and reducing consumer trust. This violation also violates consumers' rights to transparent and accurate information, as stipulated in Article 4 letter c. In addition, business actors have not carried out their responsibilities as stipulated in Article 19 of the Consumer Protection Law to provide compensation to consumers who have been harmed. Therefore, the conclusion of the study is that normatively legal protection for consumers related to the right to information is sufficient to protect, but in practice consumer rights are not fulfilled due to business actors who ignore their obligations to provide information honestly, clearly, and transparently which has an impact on material losses and reduces trust in business actors.